Keterlaksanaan Pembelajaran Efektif Melalui Peran Profesionalisme Pendidik Dalam Proses Pembelajaran - Anindita Trinura Novitasari (Journal on Education, 2022)
The learning process is an important part of implementing teaching and learning activities in every educational unit. There are several components involved including educators, students, learning media, learning designs, or methods, learning approaches, and evaluation methods at the end of learning. Teachers as the spearhead in the implementation of learning activities are highly demanded to always improve their competence and professionalism so that they can combine the motivation, interest, and enthusiasm of students in carrying out learning activities based on their similar potential, gender, and talents. The teacher’s ability in the competence of the field of knowledge possessed and the ability to implement learning pedagogy will characterize their professionalism in transfering understanding of topics or learning concepts to creating learning designs through the formulation of mature instructional objectives ar the beginning. This process will end with the implementation of the revision if the learning lesign that is created or implemented does not produce the desired output in the instructional objectivest that were formulated earlier. The cycle that is formed in the learning design reflects the sequence of learning activities that are arranged in a learning plan that begins with formulating instructional objectives, determining learning methods or designs, carrying out formative tests, perfected by summative tests, and ends with evaluating learning outcomes. The teacher or lecturer as the component closest to students who interacts with students directly is the component that most determines the success of students in receiving understanding. An effective learning system is the ultimate goal of implementing learning. The concept of teaching involves components of philosophical aspects and process aspects, based on the implementation of the teaching and learning process under the responsibility of the school in which there is the involnement of educational instructitutions and their teaching staff